COLONIZAÇÃO MICORRÍZICA DE CULTIVARES DE SOJA COM O USO DE BIOFERTILIZANTE - PEREIRA, Marceli Fernandes; FREITAS, Guilherme Jornada; Anne Mellisse Diaz, Anne Mellisse Diaz; CAPRISTO, Denise Prevedel; TORRES, Francisco Eduardo (ANAIS DO ENIC, 2018)
-